Comparative analysis of power spectrum estimation methods - Petreikytė, Gintarė; Kazlauskas, Kazys (Lietuvos matematikos rinkinys, 2010)
The subject of this paper is the comparative analysis of the eleven most important nonparametric, parametric and subspace power spectrum estimation methods. Theoretically and experimentally we analyse how the frequency resolution of the spectrum estimation methods depends on the signal length, signal-to-noise ratio (SNR) and the order parametric methods.
Keywords: power spectrum estimation; nonparametric methods; parametric methods; subspace methods; comparative analysis